2012
DOI: 10.1007/s10570-011-9648-2
|View full text |Cite
|
Sign up to set email alerts
|

Nano-dispersion of TEMPO-oxidized cellulose/aliphatic amine salts in isopropyl alcohol

Abstract: Primary aliphatic amines were introduced into most of ([95%) carboxyl groups densely present on the TEMPO-oxidized cellulose nanofibril (TOCN) surfaces via carboxyl/amine salt formation in a waterisopropyl alcohol mixture. The carbon number of alkyl chain lengths introduced into TOCN varied using n-decyl-, n-dodecyl, n-tetradecyl-, n-hexadecyl-and n-octadecyl-amines. When n-dodecyl-, n-tetradecyland n-hexadecyl-amines were used for neutralization of carboxyl groups, the TOCN-COOH/amine salts were dispersed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 25 publications
(28 reference statements)
0
24
0
Order By: Relevance
“…without the presence of TOCN-COOCaCl or TOCN-COOMgCl [29,30]. The TOCN-COOAl and TOCN-COOFe films, however, had not only the C=O absorption band at ~1600 cm -1 but also the band at 1720 cm -1 in the FTIR spectra, showing that these films have both metal carboxylate structures and some protonated carboxyls [22,25]. (Figure 3) [17,32].…”
Section: Structures Of Tocn-coom Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…without the presence of TOCN-COOCaCl or TOCN-COOMgCl [29,30]. The TOCN-COOAl and TOCN-COOFe films, however, had not only the C=O absorption band at ~1600 cm -1 but also the band at 1720 cm -1 in the FTIR spectra, showing that these films have both metal carboxylate structures and some protonated carboxyls [22,25]. (Figure 3) [17,32].…”
Section: Structures Of Tocn-coom Filmsmentioning
confidence: 99%
“…Sodium carboxylate groups are densely, regularly and position-selectively present on the crystalline TOCN surfaces. The surface modification of these carboxylate groups of TOCNs has been reported to increase the hydrophobicity of the TOCNs [20][21][22][23]. Surfactants have amphiphilic chemical structures, so the adsorption of cationic surfactants on anionic TOCN surfaces often plays an important role in efficiently making TOCNs hydrophobic without damaging the crystalline nanofibril structures.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we showed a method that was used to achieve the individual dispersion of cellulose nanofibrils in a hydrophobic PLLA matrix via the surface modification of 2,2,6,6-tetramethylpiperidiniyl-1-oxyl (TEMPO)-oxidized cellulose nanofibrils (TOCNs) [40]. Carboxyl groups are exposed in high densities on the surface of TOCNs [41,42], and 4 these groups can be used as selective anchoring sites for many kinds of functional groups [43][44][45][46][47][48][49][50]. When long PEG chains are grafted onto the carboxyl groups, the PEG-grafted TOCNs (PEG-TOCNs) can be dispersed at the individual nanofibril level in a PLLA matrix, and the resultant PEG-TOCN/PLLA composites show enhanced mechanical properties with only small amounts of the PEG-TOCNs added.…”
Section: Introductionmentioning
confidence: 99%
“…-poly(ethylene glycol) (PEG)-grafted TOCNF-COO were individually dispersed in chloroform, toluene, dichloromethane, 1,4-dioxane, DMA [15][16][17]; -n-dodecylamine-modified TOCNF-COO were dispersed at the level of individual nanofibrils in isopropyl alcohol [18]; -cetyltrimethylammonium bromide-modified TOCNFs demonstrated increased hydrophobicity and improved redispersibility in DMF [19]; -TOCNFs, modified with tannic acid and hexadecylamine, were dispersed in toluene, ethanol, acetone [20]; -TOCNF-COO with amphiphilic diblock copolymer-modified surface exhibited an increased dispersibility in such organic solvents as DMSO, DMF, ethanol, and methanol [21]. It should be noted that the aforementioned solvent exchange process is quite laborious because of the use of intermediate solvents and multiple centrifugation cycles.…”
Section: Introductionmentioning
confidence: 99%